Pengaruh Konseling Gizi Terhadap Kepatuhan Diet dan Kadar Gula Darah Sewaktu Pada Pasien Diabetes Melitus Tipe 2 - Hellen Kusumastuti; Agatha Widiyawati; Yohan Yuanta (Puslitbang Sinergis Asa Professional, 2022)
Type 2 diabetes mellitus is one of the incurable non-communicable diseases characterized by an uncontrolled increase in blood sugar levels. Type 2 diabetes mellitus requires proper management to prevent complications. The basic part of managing type 2 diabetes mellitus is nutrition counselung, with nutrition counseling can help patients in making decisions such as dietary arrangements in accordance with 3J (amount, schedule and type) and managing blood sugar levels. The purpose of this study analyzed the effect of nutritional counselung on detary complience and blood sugar levels in type 2 DM patients in kebondalem health centers. This research method is quasi experimental designs with a non-equvalent control group research design. The large number of subjects in this study was 20 people counsiting of 10 control group people and 10 experimental group people with Purposive sampling technique. Static analysis of this study using the Wilcoxon Test and Mc Nemar Test. Result showed that there was no influence of nutritional counseling on dietary compliance seen froom 3J (amount, type and schedule) in the control group while in the experimental group it showed the influence of nutritional counseling on the amount of protein and the amount of carbohidrates, but there was no effect of nutritional counseling on the amount of energy, fat, schedule and type in the experimental group, as well as the effect of nutritional counseling on blood sugar levels in the control group did not significanty and in experimental groups significanty.